Public sector facility management at military unit level: an exploratory study - Van Nieuwenhuyzen, Bernard (Department of Construction Economics and Management, 2019)
The purpose of this research is to explore the scope and understanding of facility management (FM) in the public sector, and specifically at military unit level, and compare it to a normative model. The principles of applied research are used in a single exploratory and instrumental case study with a mixed-method approach of data gathering. The literature review studied secondary data to create context, and open-ended and closed-ended questions in a questionnaire produced primary data on the actual scope and understanding of FM. A sequential mixed research approach was used to discuss the five research propositions. The research found that FM policies do not extend to military unit level. Furthermore, that FM practitioners have some understanding and competencies but there is no consistency in and between units, and therefore, support is needed in some. Support is required in the form of training/education, career development, budgets and structures as identified by FM practitioners. The Department of Defence (DOD) needs to define and communicate FM; structure FM down to unit level; staff structures; train, educate, and promote FM practitioners as FM professionals; and fund FM activities. FM practitioners need to be informed and skilled, they should build networks, and be cost conscious. This research is limited by studying FM at only a few military units on the West Coast of South Africa, which limits statistical inference and the establishment of FM within the whole of the DOD. Although FM research has been done within the South African public sector, and the DOD has made contributions, no previous research has focussed on FM at military unit level. The value of this research is a consolidated and focussed effort towards FM, which ultimately contributes to state security and the cost thereof. Future research should find the optimal structure, staffing and competencies for FM in military units.